Differential C-Q Analysis: A New Approach to Inferring Lateral Transport and Hydrologic Transients Within Multiple Reaches of a Mountainous Headwater Catchment - Arora, Bhavna; Burrus, Madison; Newcomer, Michelle; Steefel, Carl I.; Carroll, Rosemary W. H.; Dwivedi, Dipankar; Dong, Wenming; Williams, Kenneth H.; Hubbard, Susan S. (Frontiers in Water, 2020)
Concentration-discharge (C-Q) relationships have been widely used as “hydrochemical tracers” to determine the variability in riverine solute exports across event, seasonal, annual, and decadal time scales. However, these C-Q relationships are limited to investigating solute transport dynamics at individual sampling stations, such that they create an incomplete understanding of the solute behavior upstream or downstream of the sampling station. Therefore, the objective of this study is to develop, apply and assess a differential C-Q approach that can characterize spatial variability in solute behavior across stations, as well as investigate their controls, by following a different spatial scheme and organizing the river into multiple sections. The differential C-Q approach captures the difference in concentration in a river segment over the difference in discharge, thereby accounting for gains, losses or fractional solute turnover between sampling stations. Using water quality data collected over four water years (2014-18) in a mountainous headwater catchment of the East River, Colorado, this study compares traditional and differential C-Q relationships in predicting solute behavior between three sampling stations distributed throughout the river. Results from the differential C-Q analysis demonstrate significant differences in solute behavior within upstream versus downstream reaches of the East River watershed. In particular, the meandering downstream section is marked by significant gains in both groundwater and solute concentrations as opposed to the dilution and the declining trends observed in the high-relief, steep terrain upstream reach. Shale mineralogy was determined to have a major influence on in-stream concentrations pertaining to Ca, DIC, DOC, Mg, Mo, NO3 and SO4. The analyses further revealed that total P concentration in the downstream reach exceeded the U.S. Environmental Protection Agency’s desired goal for control of eutrophication (110 ppb). Overall, differential C-Q metrics yield a better understanding of the lateral storage and interactions within catchments than traditional analyses, and holds potential for aiding water quality managers in the identification of critical stream reaches that assimilate harmful chemicals.